Frecuencias alélicas y genotípicas de la variante A1/A2 del gen CSN2 (gen de la β-caseína de la leche) - Mera Mendoza, Mario Fabián (2026)
As part of the efforts to improve milk quality, different genes have been studied, such as CSN2, which encodes for β-casein. The objective of this research was to determine the genotypic and allelic frequencies of the CSN2 gene in cattle from "La Isabela de Sasapud" farm, and to analyze its effect on milk production and characteristics. The studied population consisted of 62 cows with different racial compositions: Holstein, Montbéliarde, and Jersey, from which blood samples were collected for genotype analysis. Allelic discrimination was performed using real-time polymerase chain reaction (PCR). Milk samples were also collected to measure fat and protein percentages, and to analyze the relationship between these variables and different genotypes. The genotypic frequencies were 17.74%, 67.74%, and 14.52% for the genotypes A1A1, A1A2, and A2A2, respectively, while the allelic frequencies were 51.61% for allele A1 and 48.39% for allele A2. Statistical analysis did not show significant differences between the different genotypes regarding milk production, protein percentage, and fat content, nor were significant differences found among the various racial compositions. These results indicate that the CSN2 gene should not be considered for improving milk production or quality; However, understanding the distribution of the CSN2 gene allows for make decisions during breeding to avoid the segregation of undesirable gene variants.